Cord Blood SARS-CoV-2 IgG Antibodies and Their Association With Maternal Immunity and Neonatal Outcomes - Helguera-Repetto, Addy Cecilia; Villegas-Mota, Isabel; Arredondo-Pulido, Guadalupe Itzel; Cardona–Pérez, Jorge Arturo; León-Juárez, Moises; Rivera-Rueda, Maria Antonieta; Arreola-Ramírez, Gabriela; Mateu-Rogell, Paloma; Acevedo-Gallegos, Sandra; López-Navarrete, Gloria Elena; Valdespino-Vázquez, María Yolotzin; Martínez-Salazar, Guadalupe; et al. (Frontiers in Pediatrics, 2022)
Passive transplacental immunity is crucial for neonatal protection from infections. Data on the correlation between neonatal immunity to SARS-CoV-2 and protection from adverse outcomes is scarce. This work aimed to describe neonatal seropositivity in the context of maternal SARS-CoV-2 infection, seropositivity, and neonatal outcomes. This retrospective nested case-control study enrolled high-risk pregnant women with a SARS-CoV-2 RT-PCR positive test who gave birth at the Instituto Nacional de Perinatología in Mexico City and their term neonates. Anti-SARS-CoV-2 IgG antibodies in maternal and cord blood samples were detected using a chemiluminescent assay. In total, 63 mother-neonate dyads (mean gestational age 38.4 weeks) were included. Transplacental transfer of SARS-CoV-2 IgG occurred in 76% of neonates from seropositive mothers. A positive association between maternal IgG levels and Cycle threshold (Ct) values of RT-qPCR test for SARS-CoV-2 with neonatal IgG levels was observed. Regarding neonatal outcomes, most seropositive neonates did not require any mechanical ventilation, and none developed any respiratory morbidity (either in the COVID-19 positive or negative groups) compared to 7 seronegative neonates. Furthermore, the odds of neonatal respiratory morbidity exhibited a tendency to decrease when neonatal IgG levels increase. These results add further evidence suggesting passive IgG transfer importance.